Numerical modelling intensive advanced technology-current and future scenario - Sahari, Barkawi; A. Khalid, Yousif; M. Ahmed, Elsadig; Abdul Aziz, Nuraini (Universiti Putra Malaysia Press, 2000)
In engineering design and research work, it is almost always require numerical modelling for the prediction of structural behaviour. The most common modelling tools are finite element method (FEM), boundary element method (BEM) and computational fluid dynamics (CFD). This paper deals only with FEM. A brief introduction to the finite element method as a research tool for engineers and applied scientist and brief review of the current FEM software available and their capabilities are made. It also presents the results for crash behaviour of composite cylinders and cones and push fit elastomeric steel spigot and socket joints and identifies software package houses and companies requiring specific analysis as potential source for funding. The development of material constitutive equations, integration of FEM with CAD/CAM and expert systems, application to biomechanics and medical science areas, inclusive of advanced materials and failure analysis as the main areas for research in the field of numerical modelling are also identified.